Clustering and separation of hydrophobic nanoparticles in lipid bilayer explained by membrane mechanics - Daniel, Matej; Řezníčková, Jitka; Handl, Milan; Iglič, Aleš; Kralj-Iglič, Veronika (Scientific reports, 2018)
Small hydrophobic gold nanoparticles with diameter lower than the membrane thickness can form clusters or uniformly distribute within the hydrophobic core of the bilayer. The coexistence of two stable phases (clustered and dispersed) indicates the energy barrier between nanoparticles. We calculated the distance dependence of the membrane-mediated interaction between two adjacent nanoparticles. In our model we consider two deformation modes: the monolayer bending and the hydroxycarbon chain stretching. Existence of an energy barrier between the clustered and the separated state of nanoparticles was predicted. Variation analysis of the membrane mechanical parameters revealed that the energy barrier between two membrane embedded nanoparticles is mainly the consequence of the bending deformation and not change of the thickness of the bilayer in the vicinity of nanoparticles. It is shown, that the forces between the nanoparticles embedded in the biological membrane could be either attractive or repulsive, depending on the mutual distance between them.
Keywords: Thermodynamics; zlato; kovové nanočástice; chemické modely; Lipid Bilayers; shluková analýza; Gold; Models, Chemical; lipidové dvojvrstvy; termodynamika; Cluster Analysis; Metal Nanoparticles; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions